Maintenance of metabolic homeostasis by Sestrin2 and Sestrin3. - Budanov, Andrei; Lee, Jun Hee; Talukdar, Saswata; Park, Eek Joong; Park, Hae Li; Park, Hwan-Woo; Bandyopadhyay, Gautam; Li, Ning; Aghajan, Mariam; Jang, Insook; Wolfe, Amber M.; Perkins, Guy A.; et al. (My University, 2012)
Chronic activation of mammalian target of rapamycin complex 1 (mTORC1) and p70 S6 kinase (S6K) in response to hypernutrition contributes to obesity-associated metabolic pathologies, including hepatosteatosis and insulin resistance. Sestrins are stress-inducible proteins that activate AMP-activated protein kinase (AMPK) and suppress mTORC1-S6K activity, but their role in mammalian physiology and metabolism has not been investigated. We show that Sestrin2—encoded by the Sesn2 locus, whose expression is induced upon hypernutrition—maintains metabolic homeostasis in liver of obese mice. Sesn2 ablation exacerbates obesity-induced mTORC1-S6K activation, glucose intolerance, insulin resistance, and hepatosteatosis, all of which are reversed by AMPK activation. Furthermore, concomitant ablation of Sesn2 and Sesn3 provokes hepatic mTORC1-S6K activation and insulin resistance even in the absence of nutritional overload and obesity. These results demonstrate an important homeostatic function for the stress-inducible Sestrin protein family in the control of mammalian lipid and glucose metabolism.
Keywords: Sestrins; Metabolism; Hypernutrition; Ageing; Cancer; METABOLISM; Age-related disability; Health